2016
DOI: 10.1590/s1677-5538.ibju.2015.0030
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and asymmetric dimethyl arginine (ADMA) levels in an experimental hydronephrotic kidney caused by unilateral partial ureteral obstruction

Abstract: Aim Our aim is to measure asymmetric dimethyl arginine and nitric oxide levels in rats with induced unilateral acute ureteral obstruction to research the effects on the kidney.Material and Methods The study included 21 adolescent (average age 6 weeks) Sprague-Dawley male rats weighing between 240-290g divided at random into 3 groups. Group-1: Control group (n=6): underwent no procedures. Group-2: Sham group (n=6): underwent the same procedures as the experimental group without ureter and psoas muscle dissectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…In addition to MAP restoration, TDF+NBV rats showed a significant increase in RBF and an important decrease in RVR. It is acknowledged that reduced NO production or availability is related to endothelial dysfunction, hypertension and progression of CKD ( 32 , 33 ). Renal NO is synthesized primarily by eNOS and nNOS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to MAP restoration, TDF+NBV rats showed a significant increase in RBF and an important decrease in RVR. It is acknowledged that reduced NO production or availability is related to endothelial dysfunction, hypertension and progression of CKD ( 32 , 33 ). Renal NO is synthesized primarily by eNOS and nNOS.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism involved with endothelial dysfunction includes the increase in plasma ADMA, an endogenous competitive inhibitor of NOS isoforms. Higher plasma ADMA levels are also linked to oxidative stress ( 32 , 34 ). Corroborating previous data ( 24 , 26 ), our results showed that tenofovir-treated animals exhibited augmented plasma ADMA concentration which was reversed with the administration of nebivolol.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidence provided by the present study it is concluded, that SDMA-ADMA are absolute indicators of renal dysfunction, their levels are directly affected by CM administration and the results are observed in real time. It has been reported that SDMA-ADMA are endogenous inhibitors of NO synthesis and elevated levels indicate renal damage, leading to renal hypoxia/ischemia [35]. It has also been reported that patients with chronic kidney disease (CKD) present high SDMA-ADMA levels [36], which are usually used as biomarkers of renal dysfunction in human [37].…”
Section: Discussionmentioning
confidence: 99%
“…A large increase in plasma levels of malondialdehyde (MDA) was found in patients with focal segmental glomerulosclerosis; it occurs early and could play an important role in the pathogenesis of glomerulosclerosis. Attenuation of antioxidant system is also present in patients with nephrotic syndrome, lupus nephritis, IgA nephropathy, and other glomerular diseases [13][14][15][16][17].…”
Section: Biomarkers Of Early Kidney Cell Dysfunction In Patients Withmentioning
confidence: 99%